Designing the next‐generation therapeutic vaccines to cure chronic hepatitis B: focus on antigen presentation, vaccine properties and effect measures. Issue 1 (15th January 2021) - Jansen, Diahann TSL; Dou, Yingying; de Wilde, Janet W; Woltman, Andrea M; Buschow, Sonja I
Abstract: In the mid‐90s, hepatitis B virus (HBV)‐directed immune responses were for the first time investigated in detail and revealed suboptimal T‐cell responses in chronic HBV patients. Based on these studies, therapeutic vaccination exploiting the antigen presentation capacity of dendritic cells to prime and/or boost HBV‐specific T‐cell responses was considered highly promising. Now, 25 years later, it has not yet delivered this promise. In this review, we summarise what has been clinically tested in terms of antigen targets and vaccine forms, how the immunological and therapeutic effects of these vaccines were assessed and what major clinical and immunological findings were reported. We combine the lessons learned from these trials with the most recent insights on HBV antigen presentation, T‐cell responses, vaccine composition, antiviral and immune‐modulatory drugs and disease biomarkers to derive novel opportunities for the next generation of therapeutic vaccines designed to cure chronic HBV either alone or in combination therapy. Abstract : Therapeutic vaccination exploiting the antigen presentation capacity of dendritic cells to prime and/or boost HBV‐specific T‐cell responses was deemed highly promising but has not yet delivered its promise. In this review, we summarize what has been clinically tested in terms of antigen targets and vaccine forms, how the immunological and therapeutic effects were assessed and what clinical and immunological findings were reported. We combine this information with the most recent insights on HBV antigen presentation, T‐cell responses, vaccine composition, antiviral and immune‐modulatory drugs and disease biomarkers to derive novel opportunities for the next generation of therapeutic vaccines.